Quantification of the environmental effect on citrus canker intensity at increasing distances from a natural windbreak in northeastern Argentina - Moschini, Ricardo; Canteros, Blanca Isabel; Martinez, Malvina Irene; De Ruyver, Roberto (Springer, 2022)
Citrus canker, caused by the bacterium Xanthomonas citri pv. citri (Xcc), is an endemic quarantine disease in northeastern Argentina. The objective of this study was to quantify the effect of weather variables on mid-season fruit canker intensity in an experimental grove of the “Red Blush” grapefruit cultivar in Bella Vista, Corrientes Province (Argentina), at two contrasting distances from a natural wind break (closer, wd=0; farther, wd=1). For the 1991–2010 growing seasons, disease observations were analyzed at both windbreak distances. The variable that best correlated with the disease levels (S: severe, M: moderate and L: light) at both windbreak distances was DPrecWsBl (days with recipita tion>12 mm and wind speed>2.6 km.h−1 ; Kendall Tau-b coefficient (rk)=0.71), different from the rk=0.60 obtained with DPrec (days with precipitation>12 mm). Daily wind speed values at both windbreak distances were estimated from wind speeds recorded at Bella Vista meteorological station after fitting linear regression equations. The best ordinal re sponse logistic regression models included DPrecWsBl and DT (days with temperatures in the interval 17–27 °C), and DPrec, DDMaxT (sum of the exceeding amounts of daily maximum temperature from 33ºC) and windbreak distance (wd) coded as strong (wd=0) and moderate (wd=1) wind protection (prediction accuracy=90 and 88.6 % respectively). Both models classified the nine observations with a severe canker intensity level correctly and their respective precipitation-driven predictors (DPrecWsBl and DPrec) achieved a highly satisfactory separation of two observed canker levels (S and M-L). The results may allow us to release canker risk warnings for scenarios with strong (wd=0) and moderate (wd=1) wind protection. These warnings may assist producers to make bactericide spray applications.